2021
DOI: 10.1038/s41467-021-24548-0
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids mediate polar sorting of PIN2 through phosphoinositide consumption at the trans-Golgi network

Abstract: The lipid composition of organelles acts as a landmark to define membrane identity and specify subcellular function. Phosphoinositides are anionic lipids acting in protein sorting and trafficking at the trans-Golgi network (TGN). In animal cells, sphingolipids control the turnover of phosphoinositides through lipid exchange mechanisms at endoplasmic reticulum/TGN contact sites. In this study, we discover a mechanism for how sphingolipids mediate phosphoinositide homeostasis at the TGN in plant cells. Using mul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 78 publications
1
32
0
Order By: Relevance
“…The colocalisation between the YFP signal reconstituted in BiFC (nYFP–REM and CI–cYFP) and aniline blue labelling at the PD level was quantified using the centroid object-based method using the 3D objects counter plugin of ImageJ software [ 47 ]. The resolution limit of each image was determined with a numerical aperture of 1.4 for x63 oil objective and the shorter emission maximum wavelength of the fluorophores.…”
Section: Methodsmentioning
confidence: 99%
“…The colocalisation between the YFP signal reconstituted in BiFC (nYFP–REM and CI–cYFP) and aniline blue labelling at the PD level was quantified using the centroid object-based method using the 3D objects counter plugin of ImageJ software [ 47 ]. The resolution limit of each image was determined with a numerical aperture of 1.4 for x63 oil objective and the shorter emission maximum wavelength of the fluorophores.…”
Section: Methodsmentioning
confidence: 99%
“…While the intensity of the mCIT-3xPH FAPP1 at the PM decreased already after 15 min of wortmannin treatment and became even more weaker at 90 min of treatment, the fluorescence intensity at intracellular dots was not modified even after 90 min treatment (Figure 4b,c). We previously found that metazachlor treatment causes the accumulation of PI4P at TGN [38], this accumulation was not modified by additional wortmannin treatment (Figure 4c). These results show that wortmannin impacts PI4P quantity at the PM but not at intracellular compartments.…”
Section: Metazachlor Prevents the Loss Of Pi3p Upon Inhibition Of The Phosphatidylinositol 3-kinasementioning
confidence: 58%
“…In animal cells, lipid exchange through membrane contact sites have been evidenced especially in the case of PI4P/sterol exchange [45,46]. It is unlikely that this sterol-exchange mechanism is controlled by VLCFAs in plant cells as reducing the acyl-chain length by metazachlor does not alter sterol content in microsomal or TGN-purified fraction [10,38]. We could not test this hypothesis further during the course of this study due to the technical challenge of measuring fluorescence intensity variations specifically during TGN/PI3P-positive MVB associations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the two binding sites are distinct, so it is possible to mutate the ARF1 binding site while leaving the PI4P interacting domain fully functional (He et al ., 2011). Such a mutant strictly localizes to the plasma membrane in plants (Simon et al ., 2016; Ito et al ., 2021). By contrast, mutants still able to interact with ARF1 but not PI4P localize to the TGN and not the plasma membrane (Simon et al ., 2016).…”
Section: An Inverted Balance Of Phosphatidylinositol 4‐phosphate Betw...mentioning
confidence: 99%
“…This phenotype is even stronger in sac6sac7 and sac7sac8 double mutants, SAC6 and SAC8 being closely related to the SAC7 protein (Dubois & Jaillais, 2020; Song et al ., 2021). This balance is also maintained by the activity of a phosphoinositide‐specific phospholipase C (PI‐PLC) at the TGN (Ito et al ., 2021). Chemical inhibition of PI‐PLCs increases the amount of PI4P sensors in the TGN.…”
Section: Regulation Of the Phosphatidylinositol 4‐phosphate Balance B...mentioning
confidence: 99%